Behavioral Interventions for Drug Abuse (Case Analysis of Panipahan, Rokan Hilir Regency) - Mutiara Tanila; Khairil Anwar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze drug abuse as a high-risk behavior through psychological and social perspectives and to examine effective behavioral intervention models in handling drug abuse cases. Drug abuse is considered a multidimensional social problem involving biological, psychological, social, economic, and environmental factors. The study employs a descriptive qualitative approach through literature review and theoretical analysis based on psychological and social science perspectives. The findings indicate that drug abuse is strongly associated with low self-control, cognitive distortion, social pressure, and permissive environments. In neuropsychological perspectives, addictive substances affect the brain reward system, resulting in compulsive behavior and dependence. The study also reveals that effective behavioral interventions should be implemented comprehensively through preventive, promotive, curative, rehabilitative, and structural approaches. Furthermore, collaboration among families, communities, and government institutions is essential to create sustainable social control and rehabilitation systems. Therefore, integrated behavioral intervention is considered one of the most relevant approaches in addressing drug abuse problems systematically and sustainably.